What Difference Does a Minute Make? Lessons Learned When the OSCE Bell Tolled Too Early. - Brotchie, K.; Bullock, S.; Sweet, L.; Somers, G.; Black, J.; Shuttleworth, M. (Medical Education)
The administration of an OSCE can be prone to errors, which may impact on the reliability and reproducibility of the overall examination of clinical competence (Reason, BMJ 2000; 320 768- 770). This case study describes events relating to the inadvertent ringing of the end of station bell at the 7-minute mark of an 8-minute OSCE. The decision-making involved in adjusting marks awarded for those students affected was enhanced by the immediate creation of a survey of examiners responses to the error. A timekeeping error during an OSCE affecting one-third of the student cohort was observed. Twenty-seven students were performing nine different tasks and the response by examiners was not uniform. An impromptu qualitative research study was created to assess examiners reactions and the likely effect on each student's results. Use of information from the post OSCE debrief, the overall marking scheme for each station and the examiner's survey responses were combined to make adjustments to some student's marks reducing the negative impact of the error. Many students had already completed their tasks and would not have been impacted by the shortened time. Without the use of the survey it is possible that adjustments made may have inflated the scores of undeserving students. Errors in OSCE administration do occur and require recognition of the effect on student results. Use of a timely qualitative analysis of examiners actions following an error may enable defensible adjustments to affected students' marks.